The emergence of macroscopic currents in photoconductive sampling of optical fields - Schoetz, Johannes; Maliakkal, Ancyline; Bloechl, Johannes; Zimin, Dmitry; Wang, Zilong; Rosenberger, Philipp; Alharbi, Meshaal; Azzeer, Abdallah M.; Weidman, Matthew; Yakovlev, Vladislav S.; Bergues, Boris; Kling, Matthias F. (Nature Communications, 2022)
Photoconductive field sampling enables petahertz-domain optoelectronic applications that advance our understanding of light-matter interaction. Despite the growing importance of ultrafast photoconductive measurements, a rigorous model for connecting the microscopic electron dynamics to the macroscopic external signal is lacking. This has caused conflicting interpretations about the origin of macroscopic currents. Here, we present systematic experimental studies on the signal formation in gas-phase photoconductive sampling. Our theoretical model, based on the Ramo–Shockley-theorem, overcomes the previously introduced artificial separation into dipole and current contributions. Extensive numerical particle-in-cell-type simulations permit a quantitative comparison with experimental results and help to identify the roles of electron-neutral scattering and mean-field charge interactions. The results show that the heuristic models utilized so far are valid only in a limited range and are affected by macroscopic effects. Our approach can aid in the design of more sensitive and more efficient photoconductive devices.
CRIS-Team Scopus Importer:2023-04-20